Analysis of the Use of PLN Mobile Application in Increasing Customer Satisfaction at PT PLN Persero ULP Teluk Betung - Fathia Adisa; M. Oktaviannur (Cita konsultindo, 2024)
This study aims to determine how customer satisfaction with the PLN Mobil application is affected by perceived usefulness and ease of use. The clients of PT PLN PERSERO ULP Teluk Betung make up the study's target audience. In this quantitative study, the non-probability sampling methodology used is purposeful sampling in conjunction with multiple linear regression analysis techniques using the SPSS version 29 program. The data was collected through the completion of questionnaires by 100 clients of PT PLN PERSERO ULP Teluk Betung. The study's conclusions show that perceived usefulness and ease of use have a major influence on users' happiness with the PLN Mobile application at PT PLN PERSERO ULP TelukBetung.